(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
Facies patterns of the Upper Permian and Triassic formations within the Transdanubian Range are presented. Based on surface and subsurface data, facies maps were compiled for six time slices which served as a basis of the paleogeographic reconstructions. Considering the entire Late Permian-Triassic interval, the Transdanubian Range unit shows a definite polarity: its northeastern part represents the seaward (internal) side, whereas its southwestern part represents the landward (external) side. A remarkable part of facies units of the Transdanubian Range could be correlated with time equivalent facies in the Southern Alps and the Upper Austroalpine nappes, providing an effective tool for the reconstruction of the original position of the displaced Transdanubian Range Unit.